Public financing of adult learning : Germany - Huismann, Adrienne [Verfasser]; Hippach-Schneider, Ute [Verfasser] (My University, 2025)
„This paper focuses on public financing of adult learning in Germany. It was written in the context of the ReferNet Thematic perspectives series providing national overviews of specific themes in a common format and offering comparative dimension across the EU Member States, Iceland and Norway. After introducing the main actors for adult learning (AL) and its financing, the report describes publicly financed provision of AL as well as financial support for individuals and enterprises. The current public debates on adult learning, its financing and the setting-up of individual learning accounts (ILA) are reflected. The report concludes by addressing the availability of data on AL and its financing as well as monitoring carried out.” (authors‘ abstract; BIBB-Doku)

„Dieser Beitrag befasst sich mit der öffentlichen Finanzierung der Erwachsenenbildung für Einzelpersonen und Unternehmen in Deutschland. Dabei werden die aktuellen Debatten sowie die Frage der Verfügbarkeit von Daten thematisiert.“ (Hrsg.; BIBB-Doku)
Keywords: S 4 Kosten & Finanzierung; I 2.2.1 Westeuropa; 370; Erwachsenenbildung; Finanzierung; Öffentliche Ausgaben; Bildungskonto; Internationaler Vergleich; Norwegen; Island; Bundesrepublik Deutschland; Europäische Union